INTERRELATIONSHIP BETWEEN SERVICE QUALITY, CUSTOMER LOYALTY AND CUSTOMER SATISFACTION - Yajid, Mohd Shukri Ab; Ariffin, IA; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
This study will investigate and explore between service qualities which consist of several factors that influence customer loyalty in Selangor, Malaysia which affect customer’s satisfaction. The service quality taken as perceived health, perceived price, perceived ingredients, perceived location, perceived time preparation and mediator of customer loyalty in explaining the dependent variable which is customer satisfaction on quality of burgers. The findings revealed that there is a significant impact of service quality on customer satisfaction via customer loyalty.